The legal capture of British Columbia’s fisheries: a study of law and colonialism - Harris, Douglas C. (Allard Research Commons, 2009)
This is a study of the human conflict over fish in late nineteenth and early twentieth century British Columbia, and of how that conflict was shaped by law. Law, understood broadly to include both the legal forms of the Canadian state and those of Native peoples, defined and in part created both Native and state fisheries. When those fisheries clashed, one finds conflict between legal systems. When one fishery sought to replace the other, its laws had to replace the other. Thus, this is a study of law and colonialism, seen through a close analysis of the conflict over fish. Native fisheries and the web of regulation surrounding them preceded non-Native interest in British Columbia's fish. The fishery was not an open-access resource, but rather a commons, defined by entitlements, prohibitions and sanctions that allowed certain activity, proscribed others, permitted one group to catch fish at certain times in particular locations with particular technology, and prohibited others. The Canadian state denied the legitimacy and even the existence of Native fisheries law in imposing its law on the fishery. This study, based largely on government records and a secondary anthropological literature, describes the legal apparatus constructed by the Canadian state to reduce Native control of the fisheries in British Columbia through the creation, in law, of the "Indian food fishery". Law became a means of constructing a particular economic and social order that marginalized Native participation in the fishery and eliminated Native control. It was a "rhetoric of legitimation" that supported state domination, but also local resistance. Native peoples and their supporters used law, both Native and state law, to defend their fisheries. The history of the conflict over fish is the history of competing legal cultures, and the struggle on the Cowichan River and the Babine River over fish weirs reveals those cultures, constructed in opposition to each other. The study concludes by integrating the local conflicts over fish into a wider literature on law and colonialism, reflecting on the role of law in particular colonial settings.